2014
DOI: 10.1186/1471-2261-14-95
|View full text |Cite
|
Sign up to set email alerts
|

Increased myocardial dysfunction, dyssynchrony, and epicardial fat across the lifespan in healthy males

Abstract: BackgroundEvaluation of sensitive myocardial mechanics with speckle tracking echocardiography (STE) across the lifespan may reveal early indicators of cardiovascular disease (CVD) risk. Epicardial adipose tissue (EAT) and left ventricular (LV) myocardial dyssynchrony; subclinical risk-factors of CVD, are of particular clinical interest. However, the evolution of EAT and LV-dyssynchrony across the lifespan, and their influence on myocardial dysfunction remains unclear. We aimed to establish a profile of the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
1
22
0
1
Order By: Relevance
“…Healthy men aged 19-94 were evaluated using STE echography, to study the profile of the healthy aging heart. EAT was associated with longitudinal STE LV-dyssynchrony, longitudinal strain, circumferential LV-dyssynchrony, and LV twist (54). Furthermore EAT and hepatic triglyceride content correlated negatively with peak circumferential systolic strain and diastolic strain rate in type 2 diabetes (174).…”
Section: Eat and Cardiac Geometry And Functionmentioning
confidence: 85%
“…Healthy men aged 19-94 were evaluated using STE echography, to study the profile of the healthy aging heart. EAT was associated with longitudinal STE LV-dyssynchrony, longitudinal strain, circumferential LV-dyssynchrony, and LV twist (54). Furthermore EAT and hepatic triglyceride content correlated negatively with peak circumferential systolic strain and diastolic strain rate in type 2 diabetes (174).…”
Section: Eat and Cardiac Geometry And Functionmentioning
confidence: 85%
“…A recent study by Yamaguchi and colleagues indicates that mesenchymal transformation can give rise to adipose tissue in the mouse heart [43]. In the aging human heart the increased number of adipocytes that are localized in the epicardium may suggest that they originate from PDGFRa + progenitors [44, 45]. …”
Section: Cellular and Molecular Mechanisms Contributing To Fibrosimentioning
confidence: 99%
“…8 Recent study by Crendal and co-workers demonstrated EAT is associated with altered left ventricular (LV) myocardial strain using 2-dimensional echocardiographic speckle tracking. 9 Two-dimensional speckle tracking longitudinal strain is a highly sensitive marker for subclinical myocardial dysfunction, and can predict all-cause mortality in patients with normal LV ejection fraction (EF). [10][11][12] In the present study, the authors aimed to identify independent determinants of EAT on cardiac CT in patients without obstructive CAD, and evaluate the association between EAT and myocardial systolic function using 3-dimensional (3D) speckle tracking echocardiographic multidirectional global strain analysis.…”
Section: Introductionmentioning
confidence: 99%